Persentase Serangan Hama Spodoptera frugiperda J.E. Smith (Lepidoptera: Noctuidae) pada Tanaman Jagung Manis di Kecamatan Matuari Kota Bitung - Dudurang, Biverli; Rante, Caroulus S.; Wanta, Noni N. (JURNAL ENFIT : Entomologi dan Fitopatologi, 2023)
Zea mays L. is one of the most popular crops in Indonesia. The need for corn that tends to increase with relatively high prices is a factor that triggers farmers to develop corn crop businesses. The study aimed to determine the percentage of S. frugiperda pest attack on sweet corn plantations in Matuari District, Bitung City. The results of this study are expected to provide information on the percentage of S. frugiperda pest attack for decision-making in control. This study used a survey method in three places, namely Menembo-nembo Atas Village, Sagerat Weru Dua and Tanjung Merah. The location used in this study was 0.5 ha in each village. Sampling was done by determining the size of the plot in each village consisting of 3 observation plots, each measuring 20x10 m. The age of the plants observed as the object of research was 21 wap. Observations were conducted once a week, the number of infested plants was counted and recorded. The results showed that the percentage of S. frugiperda pest attack in Matuari Subdistrict, Bitung City varied, namely in Manembo-nembo Atas Village 1.20-0.92%, Tanjung Merah Village 1.9 - 37.14% and Sagerat Weru Dua Village 1.35 - 37.55%. The percentage of S. frugiperda pest attack in Matuari Sub-district of Bitung City was an average of 8.54% with the highest attack found in Sagerat Weru Dua Village, which was 13.67%, followed by Tanjung Merah Village at 11.28% and the lowest attack was found in Sagerat Weru Dua Village. Keywords: Spodoptera frugiperda, Sweet Corn, Bitung City